THE EFFECT OF PRINCIPAL LEADERSHIP AND TEACHER COMPETENCY ON IMPROVING THE QUALITY OF EARLY CHILDREN EDUCATION (PAUD) IN PINGGIR DISTRICT - Munir Azhari; Harries Madiistriyatno; Enjang Sudarman; Santi Arah (SEAN Institute, 2022)
Education is important in human life, so the educational process can prepare and produce quality human resources in science and technology (IPTEK). The knowledge gained through the educational process can be used to face the era of globalization, so education becomes a strong foundation for developing a country through quality education. Performance or performance can be interpreted as work performance, implementation, achievement, work results, or performance. Leadership can be interpreted as influencing and directing employees to do the work assigned to them so that employees can perform the performance that their superiors have set. Motivation is a factor whose presence can lead to job satisfaction and increase productivity or individual work results. The population in this study were PAUD/RA teachers in the Pinggir Subdistrict, Bengkalis Regency, Riau Province, amounting to 36 people, so the author used a sample of 30 people. The data in this study were collected using a questionnaire. The questionnaire is a list of questions used as a guide for conducting interviews and Q&A with respondents regarding the leadership of PAUD/RA principals, teacher competence, and improving the quality of education. The research data were analyzed using linear regression analysis. The results showed that leadership and work motivation positively and significantly affected teacher performance. Based on the research, it is known that leadership produces a coefficient of 0.895. Based on the level of closeness of influence, it can be concluded that the influence of the principal's leadership on teacher performance in PAUD/RA teachers in the Pinggir District, Bengkalis Regency, Riau Province is 89.5%, classified as a strong influence. The teacher competence is known that the coefficient is 0.937. Based on the level of closeness of influence, it can be concluded that the influence of competence is 93.7%, classified as very high. As for the magnitude of the influence of the principal's leadership and competence on improving the quality of education, it is known that the correlation coefficient is 0.972. Based on the level of closeness of the influence of the two, 97.2% is classified as a very strong influence. This research implies a significant influence between leadership and teacher competence on improving the quality of PAUD/RA education in the Pinggir District, Bengkalis Regency, Riau Province. This shows that efforts to improve leadership and work motivation of the head of Madrasah Tsanawiyah must always pay attention to these three aspects. In other words, that leadership and work motivation on the performance of PAUD/RA teachers in the Pinggir Subdistrict, Bengkalis Regency, Riau Province must be adjusted and trained for teachers.